2022
DOI: 10.3390/molecules27144635
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Antioxidative Effects of Bombyx mori Silk Sericin in Cultures of Murine Retinal Photoreceptor Cells

Abstract: The availability of natural substances able to fulfill the role of antioxidants in a physiologic environment is important for the development of therapies against diseases associated with excessive production of reactive oxygen species and ensuing oxidative stress. Antioxidant properties have been reported episodically for sericin, a proteinaceous constituent of the silk thread in the cocoons generated by the larvae of the Lepidoptera order. We investigated the sericin fractions isolated from the cocoons spun … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…For biomaterial implant integration, some level of immune response can promote tissue regeneration and angiogenesis around the area of implantation. 155 Macrophages can be polarized to M1 or M2 phenotypes, with the former classified as classically activated and proinflammatory, and the latter classified as alternatively activated and anti-inflammatory. 156 The inclusion of SS in SF-SS electrospun films can increase both M1 and M2 polarization (protein and gene expression for relevant M1 and M2 markers: CCR7, CD206, MCP-1, VEGF, and others) and their secretion of cytokines (TNFα, IL-10) compared to control SF-only films in vitro .…”
Section: Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…For biomaterial implant integration, some level of immune response can promote tissue regeneration and angiogenesis around the area of implantation. 155 Macrophages can be polarized to M1 or M2 phenotypes, with the former classified as classically activated and proinflammatory, and the latter classified as alternatively activated and anti-inflammatory. 156 The inclusion of SS in SF-SS electrospun films can increase both M1 and M2 polarization (protein and gene expression for relevant M1 and M2 markers: CCR7, CD206, MCP-1, VEGF, and others) and their secretion of cytokines (TNFα, IL-10) compared to control SF-only films in vitro .…”
Section: Tissue Engineering and Regenerative Medicinementioning
confidence: 99%
“…Sericin, a protein resembling silk gum, is thought to cause some delayed hypersensitivity incidents of silk sutures in scarce circumstances [ 50 ]. Additional research using isolated sericin from silk and sericin-based biomaterials has not demonstrated that sericin is the cause of adverse effects [ 51 ]. To pinpoint the origin of any cytotoxic non-fibroin rudiments in silk and create an effective diagnostic method, thorough investigations are required.…”
Section: Features Of Silk Fibroin As a Biomaterialsmentioning
confidence: 99%
“…Although SF is the main protein used in cancer research, various studies have disclosed sericin’s therapeutic effects, including its anti-inflammatory [ 162 , 163 ] and antioxidative [ 164 ] activities. Moreover, it has been reported that sericin exhibits a great impact in anticancer research due to its cytotoxic activity, and also, it has been used for nanocarrier formulations in anticancer therapy [ 165 ].…”
Section: Sericin In Cancer Researchmentioning
confidence: 99%